2014
DOI: 10.1214/14-aos1246
|View full text |Cite
|
Sign up to set email alerts
|

On the Bernstein–von Mises phenomenon for nonparametric Bayes procedures

Abstract: We continue the investigation of Bernstein-von Mises theorems for nonparametric Bayes procedures from [Ann. Statist. 41 (2013-2028. We introduce multiscale spaces on which nonparametric priors and posteriors are naturally defined, and prove Bernstein-von Mises theorems for a variety of priors in the setting of Gaussian nonparametric regression and in the i.i.d. sampling model. From these results we deduce several applications where posterior-based inference coincides with efficient frequentist procedures, incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
228
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(241 citation statements)
references
References 41 publications
6
228
0
Order By: Relevance
“…To the best of our knowledge, examples of Gaussian priors that attain a nonparametric BvM theorem in the optimal function space are known in literature only in the SVD-based framework considered in [7,8,45], or in the 'nearly-diagonal' problem studied very recently by [41]. Applying our proof to a Gaussian prior defined via SVD would here recover the result of [45].…”
Section: A Nonparametric Bernstein-von Mises Theorem For Elliptic Bousupporting
confidence: 57%
See 2 more Smart Citations
“…To the best of our knowledge, examples of Gaussian priors that attain a nonparametric BvM theorem in the optimal function space are known in literature only in the SVD-based framework considered in [7,8,45], or in the 'nearly-diagonal' problem studied very recently by [41]. Applying our proof to a Gaussian prior defined via SVD would here recover the result of [45].…”
Section: A Nonparametric Bernstein-von Mises Theorem For Elliptic Bousupporting
confidence: 57%
“…One way of tackling the problem is to start by examining the limit behaviour of the one-dimensional marginals f , ψ W 1 | M ε instead of the full posterior. This semiparametric approach was introduced for a direct problem where A = I in [7,8], where it is shown that (approximately) in the small noise limit…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although consistency is primarily a frequentist notion, according to Blackwell and Dubins [10] and Diaconis and Freedman [17], consistency is equivalent to intersubjective agreement, which means that two Bayesians will ultimately have very close predictive distributions. Fortunately, not only are there mild conditions which guarantee consistency, but the posterior distributions can be shown to contract/concentrate at an exponential rate around the data-generating distribution (see [55] for rates of contraction of posterior distributions based on Gaussian process priors) and the Bernstein-von Mises theorem goes further in providing mild conditions under which the posterior is asymptotically normal [13,14]. The most famous of these are Doob [19], Le Cam and Schwartz [39], and Schwartz [50,Thm.…”
Section: Definition 1 For a Model Class A ⊆ M(x ) A Quantity Of Intmentioning
confidence: 99%
“…The conditions are general but difficult to verify. Deriving easier to verify sufficient conditions for the non-and semiparametric Bernstein-von Mises theorem is an active area of current research, see, for example, Bickel and Kleijn (2012), Castillo (2012), Rivoirard and Rousseau (2012), Kleijn and Knapik (2012), Kato (2013), Castillo and Nickl (2013), Castillo and Rousseau (2013), and Castillo and Nickl (2014). Misspecified semiparametric models are not covered by the existing results.…”
Section: Semiparametric Bernstein-von Mises Theoremmentioning
confidence: 99%